The Use of Video Media in Learning in Class II SDN 002 Kotobaru Kab. Kuantan Singingi - Aulia Bella Marinda; Siti Quratul Ain (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to photograph the existing phenomena by analyzing the use of video media in learning in class II SD Negeri 002 KotoBaru Kab. Kuantan Singingi. This research uses a qualitative descriptive research type. The research subjects were class teachers and second grade students at SD Negeri 002 KotoBaru. Data collection techniques in this study using observation, interviews and documentation. The data analysis technique used the Milles and Huberman model, namely qualitative data analysis consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of the study related to the use of video media that were applied in Class II SD Negeri 002 KotoBaru seemed to be able to grow attention and increase the ease of understanding the subject matter. Moreover, the use of video media in lessons received positive responses from teachers and Class II students of SD Negeri 002 Koto Baru, although there were several obstacles faced by teachers. The obstacle experienced by teachers in using video media in learning in class II SD Negeri 002 KotoBaru is that class II teachers are less able to show involvement in the media, not all materials are suitable for using video media because sometimes students have to recognize it directly. The conclusion from the results of the research that has been done is that teacher II at SD Negeri 002 KotoBaru uses video media in the learning process to provide convenience for students in learning materials, although in its use there are still obstacles in the nature of teachers in learning in class II SD Negeri 002 Koto Baru.